Simulating peculiar X-shaped extragalactic radio sources - Lacatus, D.A.; Paraschiv, A.R.; Tesileanu, O. (Advances in Astronomy and Space Physics, 2012)
Peculiar morphologies have been observed among extragalactic radio sources, which present important sideways features that are yet to be explained. After obtaining the region in the parameter space for which the intended lateral extensions appear, further 2D simulations using PLUTO code were performed. For some selected sets of parameters the effect of resolution on the simulated morphology, and the effect of a toroidal magnetic field on the propagation of the simulated jet in the stratified medium, were considered.